Health Protocols Implementation to Prevent COVID-19 Spreading in Weekarou Traditional Market’s Traders - Oskarina Hawu Lado; Marylin Susanti Junias; Daniela L. Adeline Boeky (Lontar : Journal of Community Health, 2023)
COVID-19 is a disease that attacks the respiratory tract caused by a virus that spreads through droplets or a sprinkling of phlegm. Implementation of health protocols arises to prevent COVID-19’s spreading. The behavior of traders in the market who do not follow health protocols can facilitate the transmission of COVID-19. To break the chain of COVID-19 distribution, knowledge, attitude, and action are needed. This study aims to describe knowledge, attitudes, and activities avoiding the spread of COVID-19. The design of this study uses the descriptive survey method. Data collection was taken using a total sampling technique or taken as a whole from a total population of 120 people. Analysis of the data used is univariable analysis. Based on the results of the study, it is known that the knowledge is in a suitable category, namely 55 people (45,8%), good category 45 people (37,5%), and less type 20 people ( 16,7%). The attitude is in the negative category for as many as 75 people (62,5%) and the positive category for as many as 45 people (37,5%). The actions in the Poor category, as many as 74 people (61.7%), and in the excellent category, as many as 46 people (38.3%). It is recommended that relevant agencies can be inputted and considered in making policies for implementing the COVID-19 prevention program at the Weekarou traditional market.